A Study Of Flow Characteristics On Hydraulic Physical Model Of Tawau Dam Spillway - Kamal, Nurdinie Ienani Md. (Universiti Sains Malaysia, 2021)
A dam's spillway is one of the most crucial components. It allows the project to evacuate a surplus of water in a controlled or uncontrolled manner to guarantee the project's protection. High velocity causes scouring and erosion at the downstream area by creating low or negative pressure on the spillway slab. In addition, the negative pressure produces cavitation which can cause serious damage to the structure of the spillway. To solve this issue, the suitable energy dissipator is needed to minimized the velocity of water. The purposes of this project are to study the flow characteristics and to evaluate the suitable type of energy dissipator for the Tawau Dam Spillway. The Tawau Dam spillway is a 1:30 scaled spillway physical model and it is constructed by the School of Civil Engineering, Universiti Sains Malaysia. This research was carried out for two different discharges which are 40 l/s and 73 l/s. The research also concentrated on the modification in the stilling basin by applying the suitable energy dissipator. The end sill blocks were selected as the modification in this study because they are widely used to stabilize the jumps, shorten its length and maximize energy dissipation. The velocity profile data was used to identify the flow characteristics of the Tawau Dam Spillway. Based on the findings, the flow characteristics depend on the flow discharges in the spillway model. This research implemented the Type III stilling basin, which results in the B-jump. From this case study, the most suitable size of the end sill block is (2x4) inch is used to reduce the hydraulic jump and conserve the energy of water.